Biochemical Disturbances and Profile of Lipid in Chronic Renal Failure Patients on Maintenance Hemodialysis - Raghda M. Ameer (Journal La Lifesci, 2026)
This study was conducted in AL-Hakeem Hospital in Al Najaf Al Ashraf City between January and March of 2026. 77 people, 53 men and 24 women, aged 21 to 65, were enrolled in order to assess the serum lipid profile, albumin, and hemoglobin in patients with renal failure receiving hemodialysis. The patient was diagnosed with renal failure for both sexes based on the patient's medical history, clinical examination, and renal function test findings. Medical professionals and family members who showed no signs of diabetes mellitus, hypertension, lipid issues, or renal sickness comprised the 50 control groups. There were twenty women and thirty men, ages ranging from 22 to 66. The samples of blood were obtained from the patients (8-12) hr. after night fasting. The study's discoveries include a significant alteration in the majority of variables (Lipid profile, Liver enzymes, Albumin, Urea, Uric acid, Hb, and PCV), with the exception of HDL, which was not significant. Additionally, the following changes (urea and uric acid) seem to be significantly correlated with the length of CRF disease, although the other parameters remain unchanged (TC, LDLc, HDLc, VLDLc, TG, Hb, PCV, GOT, GPT, and Albumin). On the other hand, the anova analysis of statistical analysis reveals the following: PCV vs Uric acid, PCV vs Albumin, PCV vs Hb%, GOT vs Uric acid, VLDL vs TG, Hb% vs TG, Hb% vs VLDL, LDL vs HDL), According to the current study, patients with chronic renal failure often have high TG and aberrant haematological markers.